Efficacy of Intramuscular versus Intravenous Dexmedetomidine on Attenuation of Haemodynamic Responses to Laryngoscopy and Endotracheal Intubation: A Randomised Clinical Trial - Anupama Kumari; Paras Anand; Jigisha Mehta; Sara Mary Thomas (Journal of Clinical and Diagnostic Research)
Introduction: Laryngoscopy and endotracheal intubation during anaesthesia administration provokes physiological stress responses like tachycardia, hypertension and can also lead to potential adverse events such as bronchospasm, myocardial ischaemia, arrythmias, cerebrovascular accidents etc. Dexmedetomidine, an alpha-2 adrenergic agonist has been extensively used perioperatively for stabilising intraoperative haemodynamics. Intravenous dexmedetomidine can cause major adverse effects such as bradycardia, hypotension, cardiac arrhythmias and biphasic response when used as premedication for attenuation of the laryngoscopy and intubation response which mandates exploration of other routes of administration of dexmedetomidine. Aim: To evaluate the efficacy of intramuscular dexmedetomidine and intravenous dexmedetomidine to attenuate the stress response of laryngoscopy and endotracheal intubation in patients undergoing general anaesthesia via these routes. Materials and Methods: This prospective, randomised clinical trial was single-blinded study conducted in the Department of Anaesthesia, Shrimati Bhikhiben Kanjibhai Shah Medical Institute and Research Centre (SBKS MIRC) in Piparia, Vadodara, Gujarat, India over a period of six months from January 2024 to June 2024 on 64 adult patients of American Soceity of Anaesthesiology (ASA) physical status I and II, aged between 18-60 years, posted for surgery under general anaesthesia. The patients were divided in two groups: Group DIM (intramuscular Dexmedetomidine) received Inj. Dexmedetomidine 1 μg/kg intramuscularly 45 minutes prior to induction. Group DIV (intravenous Dexmedetomidine) received Inj. Dexmedetomidine 1 μg/kg intravenously as infusion in 100 mL Normal Saline (NS) over 10 minutes 45 minutes prior to induction. Haemodynamic changes during laryngoscopy and intubation, postoperative complications and sedation score were recorded. Results: Demographic data and baseline haemodynamics were comparable between the two groups. Heart Rate (HR), Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP) and Mean Arterial Pressure (MAP) were raised from laryngoscopy and intubation in both groups. This increase was significant in Group DIV compared to Group DIM (p=0.0424, p=0.0235, p=0.0004, 0.0021, respectively). The rise in all haemodynamic parameters from laryngoscopy and intubation returned to baseline values at around three minutes in DIM group, while in DIV group they returned at around seven minutes, and remained comparable throughout. No patient experienced significant complications or sedation in postoperative period. Conclusion: Dexmedetomidine administered via intramuscular route was more effective than intravenous route at same dosage in attenuating haemodynamic stress response to laryngoscopy and intubation.